GROUNDWATER MANAGEMENT IN URBAN AREAS IN GERMANY - Coldewey, Wilhelm Georg; Kories, Holger; Thoren, Joachim ten (Águas Subterrâneas, 2000)
Huge building sites in urban areas can cause problems to the groundwater. In many cases raising or falling groundwater level can be observed. To simulate the influence of building sites to the groundwater it is usefull to simulate the situation at different stages by groundwater models. In two cases studies of urban areas in Germany a succesfull use of these models are shown. In the town of Berlin a lot of great building sites like underground routes and a lot of huge buildings in the area of Pariser Platz and Potsdamer Platz are related to the groundwater. The influence of these buildings to the groundwater is simulated by groundwater models. To minimize this influence to groundwater a Groundwater Management was installed. The task of this Groundwater Management is the reinfiltration of pumped out water in the underground, the monitoring of the groundwater level and the numerical modelling of different building states. With this Groundwater Management the risk to the vegetation of the recreationground “Tiergarten” and the foundation of huge buildings can be minimized. In the town of Bochum it was necessary to simulate the influence of an underground line to existing buildings. This was also managed by a groundwater model, with which it was possible to simulate the influence of the new underground line on the groundwater. So it was possibel to find counter meassures.